Abnormally Large Baseline P300 Amplitude Is Associated With Conversion to Psychosis in Clinical High Risk Individuals With a History of Autism: A Pilot Study - Foss-Feig, Jennifer H.; Guillory, Sylvia B.; Roach, Brian J.; Velthorst, Eva; Hamilton, Holly; Bachman, Peter; Belger, Aysenil; Carrion, Ricardo; Duncan, Erica; Johannesen, Jason; Light, Gregory A.; Niznikiewicz, Margaret; et al. (Frontiers in Psychiatry, 2021)
Psychosis rates in autism spectrum disorder (ASD) are 5-35% higher than in the general population. The overlap in sensory and attentional processing abnormalities highlights the possibility of related neurobiological substrates. Previous research has shown that several electroencephalography (EEG)-derived event-related potential (ERP) components that are abnormal in schizophrenia, including P300, are also abnormal in individuals at Clinical High Risk (CHR) for psychosis and predict conversion to psychosis. Yet, it is unclear whether P300 is similarly sensitive to psychosis risk in help-seeking CHR individuals with ASD history. In this exploratory study, we leveraged data from the North American Prodrome Longitudinal Study (NAPLS2) to probe for the first time EEG markers of longitudinal psychosis profiles in ASD. Specifically, we investigated P300 ERP component and its sensitivity to psychosis conversion across CHR groups with (ASD+) and without (ASD−) comorbid ASD. Baseline EEG data were analyzed from 304 CHR patients (14 ASD+; 290 ASD−) from the NAPLS2 cohort who were followed longitudinally over two years. We examined P300 amplitude to infrequent Target (10%; P3b) and Novel distractor (10%; P3a) stimuli from visual and auditory oddball tasks. Whereas P300 amplitude attenuation is typically characteristic of CHR and predictive of conversion to psychosis in non-ASD sample, in our sample, visual P300 (regardless of stimulus type) was enhanced in CHR/ASD+ converters(n=4), but reduced in CHR/ASD+ non-converters (n=10) as well as both CHR/ASD+- converters (n=71) and non-converters (n=219). Collapsed across sensory modalities, P3b amplitude to Target stimuli was also selectively enhanced in the CHR/ASD+ converter group, but reduced in CHR/ASD+ non-converters and in both CHR/ASD- groups. Though drawn from a small sample of CHR individuals with ASD, these preliminary results point to a paradoxical effect, wherein those with both CHR and ASD history who go on to develop psychosis have a unique pattern of enhanced neural response during attention orienting to both visual and target stimuli. Such a pattern stands out from the usual finding of P300 amplitude reductions predicting psychosis in non-ASD CHR populations and warrants follow up in larger scale, targeted, longitudinal studies of those with ASD at clinical high risk for psychosis.